Incubadora 4.0: framework para o desenvolvimento de uma incubadora virtual de empresas em instituições de ensino superior - Enke, Ernani José Fortunato Lisbôa (2022)
Business incubators located in Higher Education Institutions (HEIs) promote an entrepreneurial culture not only in their environment, but also in their surroundings, contributing to regional development. This study introduces a framework for the development of a virtual business incubator in HEIs, described as 4.0, which aims to integrate the entire institution, including the different structures and resources, physical and virtual, considering Industry 4.0 concepts and technologies, such as way to expand the access of startups and incubated companies to available services, in the context of the disruptive scenario of digital transformation, driven by the pandemic of COVID-19. The research started from a bibliometric analysis and systematic review of the literature supported by the PRISMA method, from which several models of business incubators were identified to subsidized the construction of the framework, which was submitted to the analysis by specialists who work in innovation area, linked to the Innovation Agencies and business incubators of the Federal Institutes of Education, Science and Technology. The field research was conducted based on the DELPHI method, being concluded after two rounds. It was identified that the scarce literature on virtual incubators evidences the provision of intangible services. The proposed framework runs through this characteristic, considering, in addition to the use of digital technologies in the operations of the business incubator, the remote access to such technologies by startups and incubated companies, meeting the desires of innovation managers, who identified the potential for use in their institutions, confirming its applicability. This new perspective introduced in this study, through the framework, resulted in the proposal of two concepts, Incubator 4.0 and Incubation as a Service (INaaS), where the institutional incubator, or institutional incubators network, works together with the entire structure and resources available in the different units of the HEIs, based on the use and supply of digital technologies, contributing to the technology management and innovation. Expanding the scope of services provided by such incubators contribute to develop different regions, allowing more startups and incubated companies to have access to more resources.